Health Literacy and Menstrual Hygiene Practices among Adolescent Girls (Shiksha Shastra Saurabh, 2025)
Adolescent girls must have the knowledge, skills, and confidence to get proper information about sanitation, safe hygiene practices and mensturation for better reproductive health. This study aims to investigate the menstrual hygiene and health literacy of adolescents studying in community-run secondary schools of Chandragiri Municipality. The study followed a quantitative descriptive research design. Purposive sampling was used to choose one hundred adolescents as participants studying in 11th and 12th grade, who had at least an experience of their first menstrual cycle. The data were analyzed using percentile. Primary data was collected by using the structured questionnaire. The demographic characteristics show that about 92 % participants were found between the age group of (16-17), a majority 57% demonstrated a basic level of health literacy while 18% of respondents remained below the basic level of understanding. As it is seen in the results, for 72% adolescents, their family members were the main source of knowledge. Only 58% found using sanitary pads. A transformation was observed as a majority (88%) continued to attend school despite their periods and 82% adolescent felt alone because of various restrictions (cultural/ religious/family/ etc.), particularily in the Hindu community. About 92% of the girls stated that the biggest problems were physical discomforts during menstural period. Finally, the adolescent's menstrual literacy was found from moderate to high due to the changing cultural context and fostering educational awarness. So, it can be inferred that health education must be integrated not in form but in substance in school curriculum with cultural sensitivity and practical efficiency. Initiatives to improve menstrual hygiene and health knowledge is desirable to the families, communities, and schools.